A recombination hotspot delimits a wild-species quantitative trait locus for tomato sugar content to 484 bp within an invertase gene - Fridman, Eyal (The National Academy of Sciences, 2000)
In nature, genetic variation usually takes the form of a continuous phenotypic range rather than discrete classes. The genetic variation underlying quantitative traits results from the segregation of numerous interacting quantitative trait loci (QTLs), whose expression is modified by the environment. To uncover the molecular basis of this variation, we characterized a QTL (Brix9-2-5) derived from the green-fruited tomato species Lycopersicon pennellii. The wild-species allele increased glucose and fructose contents in cultivated tomato fruits in various genetic backgrounds and environments. Using nearly isogenic lines for the QTL, high-resolution mapping analysis delimited Brix9-2-5 to a single nucleotide polymorphism-defined recombination hotspot of 484 bp spanning an exon and intron of a fruit-specific apoplastic invertase. We suggest that the differences between the Brix9-2-5 alleles of the two species are associated with a polymorphic intronic element that modulates sink strength of tomato fruits. Our results demonstrate a link between naturally occurring DNA variation and a Mendelian determinant of a complex phenotype for a yield-associated trait.